Genome-Wide Identification of Brassinosteroid Signaling Downstream Genes in Nine Rosaceae Species and Analyses of Their Roles in Stem Growth and Stress Response in Apple - Zheng, Liwei; Yang, Yingli; Ma, Shengjie; Wang, Wenming; Zhang, Jimeng; Yue, Caipeng; Wang, Yongmei; Song, Maoping; Hao, Xinqi; Huang, Jinyong (Frontiers in Genetics, 2021)
Brassinosteroid signaling downstream genes regulate many important agronomic traits in rice. However, information on such genes is limited in Arabidopsis and Rosaceae species. We identified these genes in Arabidopsis and nine Rosaceae species. They were respectively named based on chromosomal locations. Segmental duplication and whole-genome duplication under purifying selection, as determined by Ka/Ks analysis, likely contributed to Rosaceae gene expansion. Apple (Malus domestica), Arabidopsis and rice genes were generally similar. While several Rosaceae genes differed from their rice homologues in various characteristics, such as gene length, subcellular localization, transmembrane topology, conserved domains, secondary structures and responses to external signals. The brassinosteroid downstream genes in apple were respectively induced or repressed by five phytohormones. Furthermore, these apple downstream genes were differentially expressed in different apple grafting combinations (‘Nagafu No.2’/‘Malling 9’ and ‘Nagafu No. 2’/‘Nagafu No. 2’) and long-short shoot varieties (‘Yanfu No. 6’ and ‘Nagafu No. 2’). Responses of the MdBZR genes to diverse stress signals were examined and candidate hub genes were identified. These findings indicated that several brassinosteroid signaling downstream genes in Rosaceae functionally differed from their rice homologues, and certain apple genes may play roles in plant height and stress responses. This study provided valuable information and presented enriched biological theories on brassinosteroid signaling downstream genes in apple. Identification of such genes serve to help expand apple breeding and growth. This study provides useful information for brassinosteroid signaling downstream genes.